Strategie rozvoje rodinného podniku - Kořený, Dominik (Vysoké učení technické v Brně. Fakulta podnikatelská, 2014)
Tato diplomová práce se zabývá návrhem strategie rozvoje rodinného podniku Hon, a.s. Na základě analýzy současného stavu vnějšího a vnitřního okolí podniku je v souladu s hodnotami rodiny a vizí majitele formulována strategie rozvoje a v souladu s ní navrženy možnosti řešení nalezených nedostatků.

This thesis deals with proposal of strategic development of family-owned company Hon, a.s. Based on analysis of current conditions of outer and inner enviroment of the business, and in connection with family values and vision of owner, is proposed developmental strategy and possible solutions for found drawbacks.
Stategic Development of Family-owned Company
Keywords: Rodinný podnik; generační obměna; strategie; strategická analýza; SWOT; analýza rizik; Family business; generational change; strategy; strategy analysis; SWOT; risk analysis